POWER OVER CHANGE: HIGH SCHOOL SCIENCE INQUIRY IN INDIA - Cline, David (European Scientific Journal, ESJ, 2015)
The researcher was asked by the Chairman of a private school for girls in India to assist the science teachers at the school in moving classroom instruction towards a more inquiry based teaching method. The prevailing methodology at the school was that of direct instruction. The researcher, along with three undergraduate teacher candidates, conducted a series of demonstration lessons for students to engage in and for teachers to observe. After the lessons teachers from the Indian school were asked for feedback and questions. The study is framed around three concepts: risk, trust, and power. The Indian teachers are risking much in a transition to inquiry based teaching since they are bound to test scores as an indicator of effectiveness in their jobs. The researcher is a well-known figure in the Indian school that the teachers trust. The chairman of the school has the most power in this arrangement since he controls hiring and firing of teachers based on effectiveness measured by standardized tests. The key findings of this study suggest the teachers are willing to move from the direct teaching format in science instruction to an inquiry model, but are fearful of a drop in standardized test scores during the implementation period. Therefore, they would rather keep the direct instruction method that has been shown to generate high standardized test scores thus keeping their jobs. The Chairman wants an immediate move to inquiry teaching on one hand, but without a fluctuation of scores.